Kinematics Analysis of Rigid Flexible Coupling Elbow Joint Power Assisted Mechanism - Zehui Li; Shengtao Song; Fengping Ning; Ruiqin Li (Jixie chuandong)
Aiming at people cannot provide enough strength in lifting heavy objects， an urgent need of power supporting devices attached to the human body， a wearable elbow joint power mechanism with rigid and flexible coupling is proposed to provide assistance for the human body in the lifting process. It solves the problems that the traditional rigid mechanism is bulky and inflexible， and that flexible mechanisms have difficulty in supporting the weight of the human body. The configuration and characteristics of the mechanism are analyzed. The degree of freedom is calculated based on the screw theory， the closed vector method is used for position analysis. The Matlab is used to draw the change curve of flexible cable length and flexible cable tension to obtain the flexible cable length and tension at different angles. The workspace diagram is drawn， and the internal continuity of the workspace is obtained， which verify the correctness of the kinematics theory. The rigid flexible coupling elbow joint power assisted mechanism has good motion performance and can assist the elbow joint.